Spatial Temporal Analysis of Urban Heat Island and Urban Ecological Conditions Using Google Earth Engine in Tegal City, Indonesia - Audi, Fresilia; Hadibasyir, Hamim Zaky; Priyono, Kuswaji Dwi; Hakim, Rohman; Anna, Alif Noor (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
Tegal city is located on the main transportation route of Central Java's pantura and has strong trade access. Due to its strategic location, the city's significant development led to an increase in built-up land. The growth of built-up land indicates an overall increase in temperature that affects urban heat island conditions and urban ecology. The data used in this study is from Landsat 8 accessed from Google Earth Engine. The research aims to 1) analyze the phenomena of urban heat island (UHI) and 2) urban ecological conditions related to temperature based on the value of urban thermal field variance index (UTFVI). The results of the research show that spatial relationship between the East and South of Tegal City with Tegal Regency caused almost all of its territory classified as affected areas. In addition, the East Tegal area is the center of the city where all concentrations of economic activities, education centers, and government service centers in Tegal City. Linkage of Evaluation the urban ecological conditions in the aspect of land surface temperature based on UTFVI values showed the same pattern.